A Review on Antibacterial Phytochemical Constitutions Present in Aerva lanata and their Mode of Action Against Bacterial Biofilm: A Review on Antibacterial Phytochemical Constitutions Present in Aerva lanata and their Mode of Action Against Bacterial Biofilm - Rajasekaran, R. (International Journal of Pharmaceutical & Biological Archive, 2018)
Antibacterial phytochemicals have unexplored chemical structures with high therapeutic potential, additionally; phytochemicals have several advantages, including green status, different mechanisms of action from antibiotics which could help to overcome the chemotherapeutic agent resistance problem and also ability to inhibit the growth of planktonic cell and biofilm. These phytochemicals are unmatched structural diversity, and it also has no target specific. In this study, an overview of the main classes of antibacterial phytochemicals present in Aerva lanata and their mode of action against bacterial biofilm is presented. A revision about the bacterial biofilm characteristics, biofilm formation, mechanism involved against antimicrobial agents, phytochemicals properties, and their targets to eradicate biofilm, anti-biofilm properties of various phytochemicals found in A. lanata is also done. The phytochemicals such as polyphenolics interfere with the adhesion potential, quorum sensing (QS) controlled, swarming motility and biofilm formation of Escherichia coli, and Pseudomonas aeruginosa. Catechin and tannic acid also present in A. lanata were able to promote a significant reduction in biofilm formation by P. aeruginosa, and it able to block biofilm formation by E. coli and Pseudomonas putida. Antibacterial phytochemicals isolated from the different plant part of A. lanata inhibited and reduced cell-surface adhesion, methicillin-resistant bacterial biofilm formation, inhibit bacterial motility, QS, and controls biofilms of E. coli, P. aeruginosa, and Staphylococcus aureus. Phenolic acids increased the susceptibility of dual species biofilms. Peptides react against bacterial biofilm by the process of cell membrane permeabilization, intracellular targets, inhibiting nucleic acids and protein synthesis, and cell wall adhesion of Gram-negative and Gram-positive bacteria.